Farmer to farmer video: Managing seed potato (english version) - Agro-Insight; International Potato Center (2022)
This farmer-to-farmer video describes seed potato management in clear, easily understood language. Filmed in the Andes of Ecuador, this video helps the audience to understand the importance of planting good seed in healthy soil, and storing the harvest properly. This video was funded by the McKnight Foundation and produced by Agro-Insight.